Sustentabilidad económica del Comercial Escobar en el cantón Vinces periodo 2022 - Loor Carriel, María Lucia (2023)
The present case study called "Economic sustainability of Comercial Escobar in the Vinces canton, period 2022", analyzes the factors of the problem that affect the company internally and externally, the low income that the company currently has is not favorable for economic sustainability. of the commercial Through the root cause method together with the execution of technical instruments, a data collection was obtained considered through the interviews directed to the clients and the survey directed to the owner of the commercial to identify the components that generate the problem, each will be described. one of the results acquired through these instruments with the aim of presenting the best solutions, through which benefits will be obtained so that the commercial acquires a high level of economic income in the long term and promotes solutions to the problems that arise, allowing This achieves the economic sustainability necessary to keep the company in the market.